Psychometric Properties of the Sociopolitical Control Scale: A Preliminary Study on a Polish Sample - Kanafa-Chmielewska, Dorota (Department of Psychology, University of Wrocław, 2014)
The Sociopolitical Control Scale (SPCS) measures psychological empowerment at the intrapersonal level. It comprises two subscales – leadership competence (LC) and policy control (PC). Adapting SPCS to Polish cultural conditions required measuring the translation, checking comprehension of items and establishing reliability and validity. Reliability and convergent validity are sufficient enough for this measure to be used in psychological research. Confirmatory Factor Analysis lets us assume that SPCS is an appropriate measure, and the Polish scale factorial structure resembles the factorial structure of the original version. Since Poland is a socio-demographically homogeneous country, our research is significant for cross-cultural comparisons, despite a non-representative sample (n = 469). The Polish version of SPCS was developed to be used in research on the social involvement of a political, religious and humanitarian nature.
Keywords: Cross-cultural assessment; Psychological empowerment; Sociopolitical control; Psychometric evaluation